Synthesis, Scrutiny, and Applications of Bio-Adsorbents from Cockle Shell Waste for the Adsorption of Pb and Cd in Aqueous Solution - Phakakorn Panpho; Naratip Vittayakorn; Rattiphorn Sumang (My University, 2023)
Heavy metals in wastewater represent one of the most serious concerns around the world. They cause significant harm to human health. Cockle shells have been considered a source of calcium carbonate (CaCO3), but their shells are disposed of as waste that pollutes the coastal environment. CaCO3 has attracted considerable attention as an adsorbent for heavy metals. To ensure the meaningful use of cockle shell (CS) waste and achieve a zero-waste production system, in this study, CaCO3 powder was synthesized from CS. It was characterized using XRD, TA/DTA, FESEM, and AAS. The XRD results illustrated that partial phase changes occur from aragonite (natural shell) to calcite (CaCO3), calcium hydroxide (Ca(OH)2), and calcium oxide (CaO) during heating. The calcined CS presented excellent adsorption performance for Pb and Cd. The Pb removal efficiency scores were about 97%, 96%, and 99% and the Cd removal efficiency scores were 100%, 98%, and 99% in a shorter time for calcined CS at 700 °C, 900 °C, and 950 °C, respectively. The results of this study show that the calcium carbonate from CS is an effective and low-cost adsorbent for the adsorption of Pb and Cd in aqueous solution.
Keywords: Cockle; Calcium Carbonate Crystallization and Inhibition